Discussion of Appropriate Reinforcement Contingencies in the Budgeting Process - Becker, Selwyn W. (Journal of Accounting Research, 1973)
Selwyn W. Becker, Discussion of Appropriate Reinforcement Contingencies in the Budgeting Process, Journal of Accounting Research, Vol. 11, Empirical Research in Accounting: Selected Studies 1973 (1973), pp. 254-256